AKUNTANSI FORENSIK DALAM UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI - WIRATMAJA, I DEWA NYOMAN (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 2 (2010), 2010)
Corruption has become a phenomenal issue and always interesting to discuss in Indonesia. Corruption has been considered as the root cause of national problems, such as high cost economy, economic growth, and investment barrier. This article focuses on the chance of implementing forensik accounting concept in providing evidence to support court decision. The discussion aims to review the role of forensik accounting through preventive, detective, and corrective approaches to prevent and handle corruption in Indonesia. Cressey’s model of fraud triangle is used to map forensik accounting roles in preventing corruption.
Keywords: fraud triangle, corruption, evidence, court